A webquest como ferramenta de aprendizagem no contexto escolar - Alves, Robson José Gomes (2016)
For the internet to be seen as a useful tool in the aid of school research, resources should be made available to guide the student because of the numerous activities that are normally requested in a school context. Given this preeminent need, we decided to carry out this study, observing of the use of Webquest by the students and using a group questionnaire as our main study source. As a complementary source, the teacher‟s point of view on the application of this methodological resource and its results was used, aiming to improve teaching. This proposal, anchored in the theoretical assumptions postulated by Lévy (2010), Marcuschi and Xavier (2005), and Moran (2013), seeks to verify the role of Webquest as facilitator on internet research process by 8th grade students in a public school in the city of Campina Grande, Paraíba; to improve the digital literacy of students participating in this research; to check if the use of Webquests provides the cooperative and/or collaborative work in the school context; and to investigate the role of the teacher in the use of this technological tool in the classroom context. The methodology guiding the research was defined from a qualitative nature, as a way of giving voice to the people involved. This type of research allows researchers to obtain descriptive data through direct and interactive contact with the situation under study and enables them to understand phenomena according to the perspective of the participants on the studied situation. From that point, the researchers can situate their interpretations. In the case of this research project, it is necessary to situate and construct dynamism of approximation to the process of knowledge acquisition through the internet for school research. Hence, the option of performing an action research with the insertion of the Webquest tool. The learning context promoted by the said Webquest alludes to practices that put the learner in contact with diverse knowledge within authentic activities of language use, which makes the student reflect and interact with these subjects, so as to build discursive competence between the learner and others.